2019
DOI: 10.1590/1679-395173826x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Career Couples and Their Inclinations Regarding Work and Family: The Brazilian Scenario

Abstract: This study aims to explore the database of the National Household Sample Survey (PNAD) produced by the IBGE (Brazilian Institute of Geography and Statistics) in order to investigate how couples from a dual-career perspective approach the demands of home and work. The study uses a quantitative-descriptive analysis of secondary data to update the model proposed by Berlato (2015), in which typologies were delineated from a sample of dual-career couples who were former students of a state university in São Paulo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Numerous studies have consistently shown that women, especially those working fewer hours, bear the primary responsibility for home maintenance and caregiving roles, in contrast to men [24,28,[52][53][54][55]. This finding helps explain our results, as mothers working full-time may receive support from their husbands in managing their work responsibilities, and if this support is not available, they may seek external assistance for home maintenance to fulfill their job requirements [24,26,28,52,56].…”
Section: Time-use Within Occupational Rolesmentioning
confidence: 56%
See 1 more Smart Citation
“…Numerous studies have consistently shown that women, especially those working fewer hours, bear the primary responsibility for home maintenance and caregiving roles, in contrast to men [24,28,[52][53][54][55]. This finding helps explain our results, as mothers working full-time may receive support from their husbands in managing their work responsibilities, and if this support is not available, they may seek external assistance for home maintenance to fulfill their job requirements [24,26,28,52,56].…”
Section: Time-use Within Occupational Rolesmentioning
confidence: 56%
“…Achieving time-use balance can be particularly challenging for mothers, as they are the ones who face the greatest struggle in reconciling work and family responsibilities [17,[23][24][25][26]. As a result, many mothers opt for part-time employment as a means to harmonize their various roles [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%